Potencial de novas cultivares de Coffea arabica L. resistentes à ferrugem para a produção de cafés especiais - Fassio, Larissa de Oliveira (2014)
In order to meet the high demand for special coffees imposed by the international and national markets, it is justifiable to search for genetic material, which in addition to presenting productivity and pathogen resistance characteristics, present better beverage quality characteristics and, to define these quality characteristics, it is necessary to know the sensorial and chemical profile of the coffee beans. Therrefore, this study had the objectives of: evaluating the sensorial characteristics cultivars resistant to rust for the production of special coffees; assess whether there is a relation between the contents of caffeine, trigonelline and 5-CQA; evaluate the fatty acid profile with the beverage’s sensory attributes; and with these analyses, allow the differentiation of cultivars in two locations of Minas Gerais, Brazil. For this purpose, we analyzed seven C. arabica cultivars bearing rust resistance, developed by the EPAMIG breeding program in partnership with UFV and UFLA, and two susceptible cultivars (Yellow Bourbon and Topazio MG1190) in two cultivation environments: Lavras, southerm Minas Gerais and Patrocínio, Cerrado region of Minas Gerais. The experiments were installed on the field in a randomized block design (RBD) with three replicates and plots consisting of ten plants each. We applied multivariate analysis (Principal Component Analysis) for better interpretation of the results. The acidity and flavor attributes were determining factors for differentiating the cultivars and the interaction between them and the evaluated environments. The Araponga MG1, Catiguá MG2 and Catiguá MG1 cultivars are the most indicated for the production of special coffee in Minas Gerais. The contents of caffeine, trigonelline and 5-CQA did not present a good correlation with the fragrance, flavor, acidity, body and final score attributes. However, these compounds allowed us to differentiate the environments. Among the fatty acids found in the grains, capillary gas chromatography detected the presence of an unusual acid in coffee, gamma-linolenic acid (C18: 3 ω-6, GLA). The palmitic, linoleic and palmitoleic fatty acids presented correlation with the sensory quality of the beverage while the unsaturated fatty acids, linoleic, linolenic and gamma-linolenic acids, were able to discriminate the Patrocínio environment.